Media Exposure to and Knowledge of the BCG Economic Development Policy Model of the Thai People - Wansom Seesung (Jurnal Komunikasi Pembangunan, 2021)
This study investigated the media exposure and knowledge of the BCG economic development policy model among the Thai people. An online questionnaire was used to collect data from 496 Thai respondents. The frequency distribution, percentage, mean and standard deviation were used to analyze the data. It was found that among thirteen channels, the majority of the respondents were exposed to the BCG model information through websites (47.72%), followed by Facebook (45.23%), and the least, to clubhouse and radio (3.73% for both). As for the frequency of exposure, the majority of the respondents were exposed to media for information about the BCG policy model from time to time depending on the occasion, followed by 4-5 times a month, and the least exposed at all times. Regarding the quality of information dissemination, data analysis revealed that the respondents indicated the quality at a moderate level in all aspects. Analysis of the responses of eight questions about the BCG model revealed that the majority of the respondents had a low level of knowledge of the BCG policy model, followed by a moderate level, and a high level of only 2.1%.